Atmospheric corrosion of outdoor bronze artefacts: the case study of 'Katarsis', by Magdalena Abakanowicz. Issue 1 (1st April 2022) - Sebar, Leila Es; Iannucci, Leonardo; Parvis, Marco; Grassini, Sabrina; Angelini, Emma
Abstract: The conservation of cultural heritage metallic items is deeply connected to the investigation of the corrosion phenomena affecting the metallic surface and to the study of the influence of the surrounding environmental parameters. This paper describes the case study regarding the metallic artwork 'Katarsis' of the Gori Art Collection at Fattoria di Celle (Pistoia, Italy), created by the artist Magdalena Abakanowicz. An in-situ multi-analytical approach was employed in order to assess the conservation state of the statues and to ensure their long-lasting preservation. In particular, X-rays fluorescence (XRF), Raman spectroscopy (RS), and X-Rays diffraction (XRD) were used for the identification of the corrosion products, mainly sulphates, and to identify the employed alloy. In this paper, the preliminary results will be presented and discussed.